Producer-client paradigms for defense intelligence. Issue 1 (2nd January 2023) - Pothoven, Saskia; Rietjens, Sebastiaan; de Werd, Peter
ABSTRACT: This article examines how specific characteristics of defense intelligence affect the relationship between intelligence producers and their clients in a manner that is different from prevailing conceptualizations commonly found in civilian intelligence organizations. To do so, the paper first addresses some important distinguishing characteristics of defense intelligence. These include the embedded character of defense intelligence agencies in military organizations, specific military cultural traits and the mixture of military and civilian personnel. Based on literature study and desk research, the paper then identifies three producer-client paradigms: I) distance versus closeness, II) the ideal of analytic objectivity, and III) intelligence lays the foundation for decision-making . Confronting these paradigms with the characteristics of defense intelligence, we find that defense intelligence producer-client relations are more multifaceted, layered and networked than commonly explained.